The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jpsychires.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the depression item bank from the Patient-Reported Outcomes Measurement Information System (PROMIS®) in a three-month observational study

Abstract: The Patient-Reported Outcomes Measurement Information System (PROMIS®) is an NIH Roadmap initiative devoted to developing better measurement tools for assessing constructs relevant to the clinical investigation and treatment of all diseases—constructs such as pain, fatigue, emotional distress, sleep, physical functioning, and social participation. Following creation of item banks for these constructs, our priority has been to validate them, most often in short-term observational studies. We report here on a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(257 citation statements)
references
References 22 publications
8
246
1
2
Order By: Relevance
“…Correlations among PROMIS Depression and anxiety measures were located on the upper bound of the moderate level range, and were lower than those between the PHQ-9 and the anxiety measures. Previous studies, in general population (Cella et al, 2010;Pilkonis et al, 2011) and patient samples (Amtmann et al, 2014;Bajaj et al, 2011;Pilkonis et al, 2014) found similar results, with moderate to high correlations of PROMIS Depression with other anxiety measures. The fact that in our study PROMIS Depression measures were able to discriminate between depression and anxiety, with large effect sizes among individuals with depression, and small effect sizes in patients with GAD or panic without depression supports high discriminant and diagnostic validity of the instrument.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Correlations among PROMIS Depression and anxiety measures were located on the upper bound of the moderate level range, and were lower than those between the PHQ-9 and the anxiety measures. Previous studies, in general population (Cella et al, 2010;Pilkonis et al, 2011) and patient samples (Amtmann et al, 2014;Bajaj et al, 2011;Pilkonis et al, 2014) found similar results, with moderate to high correlations of PROMIS Depression with other anxiety measures. The fact that in our study PROMIS Depression measures were able to discriminate between depression and anxiety, with large effect sizes among individuals with depression, and small effect sizes in patients with GAD or panic without depression supports high discriminant and diagnostic validity of the instrument.…”
Section: Discussionsupporting
confidence: 71%
“…Of greatest concern is the evaluation of construct validity and responsiveness in patient samples relevant to the construct of interest. PROMIS Depression has shown good results in patients with major depression (Pilkonis et al, 2014) and other conditions (Amtmann et al, 2014). However, the psychometric properties of the PROMIS Depression measures in Spanish or other language versions have not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…None of the items were related to social connectedness, loneliness, or social isolation. The PROMIS Depression Scale has shown good convergent validity through its significant correlations, across multiple time points, with the Patient Health Questionnaire-9 and the Center for Epidemiologic Studies Depression scale (correlations ranged from .72 to .84; Pilkonis et al, 2014). Further, it demonstrated good reliability (alpha = 0.94) in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…[28] Specifically, the PROMIS depression scale has been correlated and validated with other commonly used depression instruments, including the Center for Epidemiological Studies Depression Scale (CES-D), the Beck Depression Inventory (BDI-II), and the Patient Health Questionnaire (PHQ-9). [29,30] The 4-item PROMIS depression scale asked participants how frequently in the past 7 days they had experienced depression, including feeling hopeless, worthless, helpless, or depressed. [31] These items were scored on a 5-point Likert scale ranging from 1 to 5, corresponding to responses of “Never,” “Rarely,” “Sometimes,” “Often” and “Always.” Thus, the total possible raw score was between 4 and 20.…”
Section: Methodsmentioning
confidence: 99%